Analisis Kemampuan Berpikir Kritis Siswa SMA Dalam Menyelesaikan Masalah Logaritma Berdasarkan Gaya Kognitif Visualizer-Verbalizer - Sintiya, Ambar; Hasan, Buaddin; Affaf, Moh. (Universitas Dr. Soetomo, 2021)
Abstract The implementation of the 2013 revised curriculum requires students to be able to think critically. The field of mathematics, especially logarithmic material, contains many characteristics, so it requires the ability to think critically to solve the problem. Meanwhile, the ability to think critically is influenced by students' cognitive styles, such as the visualizer and verbalizer cognitive styles. So it is necessary to do research to analyze students' critical thinking skills in solving logarithmic problems viewed from the two cognitive styles. This qualitative descriptive research is used by the teacher as a learning design or strategy so that it can improve students' critical thinking skills according to their cognitive style. The subjects are class X students of SMAN 1 Kamal with visualizer and verbalizer cognitive style. The data analysis technique begins with the VVQ cognitive style test (Visualizer-Verbalizer Questionnaire), problem-solving tests, and interview tests. The results obtained by the visualizer subject in TPM 1 were 14 (good critical thinking category), and TPM 2 scored 12 (adequate critical thinking category). While the verbalizer subject in TPM 1 has a score of 13 (adequate critical thinking category), and TPM 2 is 9 (adequate critical thinking category). Based on the research results, it can be concluded that the critical thinking ability of the visualizer subject dominates compared to the verbalizer subject, because it is able to detect inconsistencies and solve problems systematically. Keywords: Thinking, Critical, Visualizer, Verbalizer, Logarithm. Abstrak Penerapan kurikulum 2013 revisi menuntut siswa untuk mampu berpikir kritis. Bidang matematika khususnya materi logaritma memuat banyak sifat, sehingga diperlukan kemampuan berpikir kritis untuk memecahkan masalahnya. Sementara, kemampuan berpikir kritis dipengaruhi oleh gaya kognitif siswa, seperti gaya kognitif visualizer dan verbalizer. Sehingga perlu dilakukan penelitian untuk analisis kemapuan berpikir kritis siswa dalam menyelesaikan masalah logaritma ditinjau dari kedua gaya kognitif tersebut. Penelitian deskriptif kualitatif ini digunakan guru sebagai rancangan ataupun strategi pembelajaran sedemikian sehingga dapat meningkatkan kemampuan berpikir kritis siswa sesuai gaya kognitifnya. Subjek merupakan siswa kelas X SMAN 1 Kamal dengan gaya kognitif visualizer dan verbalizer. Teknik Analisis data diawali dengan tes gaya kognitif VVQ (Visualizer-Verbalizer Quistionnairre), tes penyelesaian masalah, dan tes wawancara. Hasil yang diperoleh subjek visualizer dalam TPM 1 adalah 14 (Kategori berpikir kritis baik), dan TPM 2 bernilai 12 (Kategori berpikir kritis cukup). Sedangkan subjek verbalizer dalam TPM 1 memiliki nilai 13 (Kategori berpikir kritis cukup), dan TPM 2 bernilai 9 (Kategori berpikir kritis cukup). Hasil penelitian menyimpulkan bahwa kemampuan berpikir kritis subjek visualizer mendominasi dibanding subjek verbalizer, dikarenakan mampu mendeteksi inkonsistensi dan menyelesaikan permasalahan secara sistematis. Kata Kunci: Berpikir, Kritis, Visualizer, Verbalizer, Logaritma.